Pityriasis lichenoides-like lesions with perifolliculitis in Lyme borreliosis. - Menni, S.; Pistritto, G.; Gelmetti, C.; Stanta, G.; Trevisan, G. (European Journal of Pediatric Dermatology, 2018)
A 13-year-old girl presented cutaneous lesions reminiscent of pityriasis lichenoides, associated with headache and fever. The clinical features raised the suspicion of Lyme borreliosis due to their occurrence three months after a trip in an endemic area. The diagnosis of Lyme borreliosis was confirmed by the demonstration of spirochete-like bodies inside the lesions with Warthin-Starry silver stain and by identifying B. burgdorferi flagellar genoma in the affected skin with polymerase-chain reaction. The Authors discussed the diagnosis, prognosis and therapy of this unique case of Lyme borreliosis.